Implementasi Kalman Filter Dalam Teknik Hand Tracking Sebagai Kontrol Pointer Mouse Komputer - Yuza Reswan; Dedy Agung Prabowo (Jurnal Sistem Informasi, 2018)
ABSTRACTIn their daily life, humans usually use hands for the interaction between humans and machines or humans andhuman so that the human-computer interaction and computer-based Computer Vision using fingers has more valuethan using other objects. Many techniques are developed based on the Computer Vision model, one of the techniquethat is implemented in this field is Hand Tracking. The use of such techniques uses certain algorithms to improveperformance, one of which is the filter algorithm. Kalman Filter is an estimator algorithm in which informationfrom an object is detected in a frame and the status of the object in the previous frame to create an approximatestatus of the new state of the object so that the process of unstable object movements in the tracking process thatoccurs due to noise can be minimized by the kalman filter. The use of Hand Tracking techniques and Kalman Filteralgorithm is expected to meet the needs of more advanced human and computer interactions. The results of thisstudy are expected to be useful as a means of scientific development in the field of informatics engineering and theability to build software in the field of Hand Tracking techniques and Kalman Filter algorithm as well as expectedThis application can be used for personal or public interest.Keywords: Computer Vision, Hand Tracking, kalman FilterABSTRAKDalam kesehariannya, manusia seringkali menggunakan tangan untuk interaksi antara manusia dan mesin ataupunmanusia dengan manusia sehingga interaksi manusia dan komputer berbasis Computer Vision mengunakan jaritangan memiliki nilai lebih dibandingkan menggunakan objek lain. Banyak teknik yang dikembangkan berdasarkanmodel Computer Vision, salah satu teknik yang sering diimplementasikan dalam bidang ini adalah Hand Tracking.Sering kali penggunaan teknik tersebut menggunakan algoritma tertentu untuk meningkatkan kinerjanya, salahsatunya adalah algoritma kalman filter. Kalman Filter adalah sebuah algoritma estimator yang dimana informasidari objek terdeteksi di suatu frame dan status objek tersebut pada frame sebelumnya untuk membuat statusperkiraan dari status baru objek tersebut sehingga proses pergerakan objek yang tidak stabil pada proses trackingyang terjadi karena noise dapat diminimalkan oleh kalman filter. Penggunaan teknik Hand Tracking dan algoritmaKalman Filter diharapkan mampu memenuhi kebutuhan interaksi manusia dan komputer yang lebih maju. Hasilpenelitian ini diharapkan berguna sebagai sarana pengembangan keilmuan dalam bidang teknik informatikadan kemampuan dalam membangun perangkat lunak pada bidang teknik Hand Tracking dan algorita KalmanFilter serta diharapkan Aplikasi ini dapat digunakan untuk kepentingan pribadi maupun umum.Kata Kunci : Computer Vision, Hand Tracking, kalman Filter